ENGLISH LINGUISTICS TERMINOLOGY: SCOPE, EVOLUTION AND CHALLENGES - Razoqova Kumush Sadriddinovna (PEDAGOGS, 2025)
Abstract: Terminology is the lifeblood of linguistics as an academic discipline and in its professional application. For English linguistics, the development and standardization of terminology lagged behind that of the discipline and all its sub-disciplines such as phonetics, morphology, syntax, semantics, pragmatics, and sociolinguistics. The aim of this paper is to examine the nature, function, and issues of linguistic terminology in English, clarifying its etymology, borrowing and neologisms, and ambiguity and standardization problems. Moreover, the importance of terminological precision in linguistic research and pedagogy is also dealt with.